Sub‐Annual to Interannual Arabian Sea Upwelling, Sea Surface Temperature, and Indian Monsoon Rainfall Reconstructed Using Congruent Micrometer‐Scale Climate Proxies. Issue 3 (23rd March 2022) - Napier, Tiffany J.; Wörmer, Lars; Wendt, Jenny; Lückge, Andreas; Rohlfs, Nina; Hinrichs, Kai‐Uwe
Abstract: The Indian monsoon system impacts over 1 billion people, and rainfall from its southwest monsoon is critical for agriculture. Cool sea surface temperatures (SSTs) in the Arabian Sea have been associated with reduced monsoon rainfall and vice versa, although this relationship is difficult to examine due to scarce and short instrumental records. We utilize laminated Pakistan Margin sediments to reconstruct southwest monsoon rainfall and Arabian Sea SSTs at sub‐annual to multi‐annual resolution for the twentieth century. We applied paired sub‐mm mapping techniques to intact sediment core surfaces to measure elemental abundances and lipid biomarkers. The first principal component of the elemental results (PC1) explains 47% of the elemental variance and is driven by detrital lithogenic elements K, Ti, and Fe. PC1 is positively correlated with homogeneous India June‐September rainfall departures from 1903 to 1928 and 1949–1970 on a multi‐annual scale. Correlations in the remaining timespans are either negative or absent, likely driven by a combination of dam and barrage construction on the Hub and Indus Rivers and negative rainfall departures. We propose PC1 as a proxy for southwest monsoon rainfall on multi‐annual timescales prior to ∼1930. A dampened annual SST cycle is resolved with the alkenone U 37 K ′ U_37^K^′ paleothermometer, which also captures the interannual‐decadal trends of twentieth century Arabian Sea SSTs. We propose the crenarchaeol‐caldarchaeol tetraether index, sourced from planktonic Thaumarchaeota, as a delayed upwelling proxy for the western Arabian Sea. Our reconstructions corroborate the established relationship of reduced Arabian Sea upwelling leading to warmer SSTs and increased monsoon rainfall, and vice versa. Plain Language Summary: The Indian monsoon impacts over 1 billion people, particularly through its summer monsoon rains that are critical for agriculture. Summer monsoon rainfall is difficult to predict because it is not spatially or temporally consistent each year, and climate models do not simulate it well. However, it is known that cool seawater surface temperatures in the Arabian Sea in summer lead to reduced monsoon rainfall, while warm seawater surface temperatures in the summer lead to more rainfall. Marine algae respond to seawater temperature changes by altering the proportions of molecules in their cells, which are preserved in seafloor sediments. We used this relationship to reconstruct approximately monthly Arabian Sea water surface temperature for the twentieth century. Seawater surface temperatures in the Arabian Sea are made cooler in the spring and summer when cold, deep waters are brought up to the sea surface during upwelling. We reconstructed upwelling by measuring changes in the molecules produced by planktonic archaea in their cell membranes. We reconstructed yearly monsoon rainfall using the elemental signature of river sediments preserved in the same seafloor sediments. Our reconstructions confirm that increased upwelling cools the Arabian Sea and reduces monsoon rainfall and vice versa. Key Points: We present an annually‐resolved, detrital lithogenic element‐based proxy for southwest Indian monsoon rainfall Alkenone paleothermometer records a muted seasonal sea surface temperature cycle; archeal lipid distribution an indirect upwelling proxy Our reconstructions capture the upwelling‒sea surface temperature‒monsoon rainfall relationship identified in models and observations